A high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution and its application

By adding specific additives to the plating solution, a high-hardness nano-Ni-Co-B alloy chromium-substitute electroplating solution is prepared, which solves the existing technology problems of insufficient demand for hard chromium replacement, complex composite plating processes, and insufficient performance of nickel-based alloys. Achieving coating effects of high hardness, corrosion resistance and efficient deposition.

CN115613087BActive Publication Date: 2025-01-21HARBIN INST OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211313821.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-25
Publication Date
2025-01-21
Estimated Expiration
2042-10-25

AI Technical Summary

Technical Problem

The existing trivalent chromium plating cannot meet the needs of hard chromium substitute. The composite plating process is complex and the current distribution is uneven. Nickel-based alloys have problems such as large internal stress, low hardness and slow plating speed.

Method used

Develop a high-hardness nano-Ni-Co-B alloy chromium-substitute electroplating solution, and form a high-quality nano-plating by adding grain refiners, stress relievers and wetting agents to the plating solution.

Benefits of technology

The high hardness (1100~1300HV-50), corrosion resistance and brightness of the coating are achieved, the cathode current efficiency reaches 95%, the deposition speed is 70~80μm/h, and the use of hexavalent chromium is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115613087B_ABST
    Figure CN115613087B_ABST
Patent Text Reader

Abstract

A high-hardness nano Ni-Co-B alloy chromium-substitute electroplating solution and its application, which belongs to the field of electroplating, and specifically relates to a high-hardness nano Ni-Co-B alloy chromium-substitute electroplating solution and its application. The purpose of the present invention is to solve the problem that the existing trivalent chromium electroplating cannot meet the demand for hard chromium, the composite plating process is complicated, and the uneven current distribution leads to uneven coating thickness. Its large-scale application is still subject to great restrictions and nickel-based alloys have problems such as large internal stress, low hardness and slow plating speed. A high-hardness nano Ni-Co-B alloy chromium-substitute electroplating solution is prepared from a main salt, a boron source, an anode activator, a pH buffer, a grain refiner, a stress reliever, a wetting agent and distilled water. The Ni-Co-B alloy chromium-substitute coating prepared by a high-hardness nano Ni-Co-B alloy chromium-substitute electroplating solution can reach a hardness of 1100 to 1300 HV-50.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electroplating, and in particular relates to a high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution and application thereof. Background Art

[0002] As one of the indispensable processes in the electroplating industry, hexavalent chromium electroplating technology is widely used. When used as a protective-decorative coating, it has the advantages of bright color and good anti-discoloration ability; in addition, due to the advantages of high hardness, good wear resistance, and good corrosion resistance, the chrome plating layer is widely used in engine cylinders and piston rings, roller surfaces of embossing rollers, and inner cavities of guns. However, hexavalent chromium electroplating technology also has some disadvantages that limit its application. For example, the cathode has severe hydrogen evolution, low current efficiency, high current and high voltage deposition, high toxicity of hexavalent chromium, and difficulty in wastewater treatment. It is very necessary to find a green and environmentally friendly alternative chrome plating layer and process method that meets or even exceeds the performance of chromium (VI) plating.

[0003] Nano-coatings have unique physical and chemical properties, such as high corrosion resistance, high hardness, and high wear resistance, due to the significant reduction in grain size and the presence of a large number of grain boundaries between adjacent grains. In the electroplating process, it is usually necessary to add suitable additives to increase the cathode polarization, increase the nucleation rate of the crystal nucleus, and make the grains finer, thereby obtaining a nano-coating. Therefore, the primary problem in preparing nano-coatings is to develop suitable non-toxic additives that significantly increase the cathode polarization under the blocking effect or penetration effect of the additives. Adding a small amount of additives to the plating solution can greatly improve the performance of the coating. Depending on the type of additive, it plays a role in grain refinement, leveling, wetting, and stress relief.

[0004] At present, the chromium replacement technology mainly includes trivalent chromium electroplating process, composite electroplating process and alloy electroplating / chemical plating process. Among them, trivalent chromium electroplating has been increasingly used in the field of decorative chromium replacement due to its low toxicity, high dispersibility and covering ability. However, this technology cannot meet the demand for replacing hard chromium. Using composite electroplating technology, adding insoluble hard phase particles to the plating solution can significantly improve the hardness of the coating. For example, the hardness of Ni-diamond and Ni-Co-diamond composite coatings can reach 700HV. However, the composite plating process is complicated, and the uneven current distribution leads to uneven coating thickness, so its large-scale application is still subject to great restrictions. Nickel-based alloys have the advantages of bright appearance, high hardness, high wear resistance, and high corrosion resistance, making them the most promising coating to replace hard chromium. However, the nickel-tungsten alloys, nickel-cobalt alloys, nickel-boron alloys, nickel-molybdenum alloys, etc. currently under study still have problems such as large internal stress, low hardness, and slow plating speed. Summary of the invention

[0005] The purpose of the present invention is to solve the problems that the existing trivalent chromium electroplating cannot meet the demand for replacing hard chromium, the composite plating process is complicated, and the uneven current distribution leads to uneven coating thickness, and its large-scale application is still subject to great restrictions. In addition, the nickel-based alloy has the problems of large internal stress, low hardness and slow plating speed, and to provide a high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution and its application.

[0006] A high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution is prepared from a main salt, a boron source, an anode activator, a pH buffer, a grain refiner, a stress reliever, a wetting agent and distilled water;

[0007] The main salts are nickel salt and cobalt salt;

[0008] The grain refiner is one of 2-ethylamino-4-methylthiazole-5-carboxylic acid, polyethyleneimine, myrcene, allyl furoate, 3-(methylthio)hexanol acetate or a mixture of several thereof;

[0009] The stress relieving agent is 1,3-dicyclohexyl imidazole chloride, 2-methoxy-4-vinylphenol or Bengal rose red;

[0010] The wetting agent is polyethylene glycol, OP emulsifier or sodium lauryl sulfate.

[0011] A high-hardness nano Ni-Co-B alloy chromium-substitute electroplating solution is used for preparing a Ni-Co-B alloy chromium-substitute plating layer.

[0012] Principle of the present invention:

[0013] The grain refiner of the present invention forms an extremely thin adsorption layer on the cathode surface through adsorption, which hinders the discharge of metal ions and thus improves cathode polarization; the grain refiner adsorbed on the cathode surface will hinder or even completely inhibit the growth of crystals, so new crystals are generated at other locations; by repeating this process, a high-quality coating with fine and bright grains can be obtained;

[0014] The stress relieving agent of the present invention can make the coating produce a certain compressive stress, thereby offsetting the tensile stress in the coating, improving the ductility of the coating, preventing the generation of micro cracks on the surface of the coating, and improving the brightness of the coating;

[0015] The addition of the wetting agent of the present invention can reduce the surface tension of the electrode / solution interface, improve the wetting performance of the electrolyte on the electrode surface, and make it easier for metal ions to deposit on the cathode; at the same time, hydrogen bubbles are separated from the electrode surface when they are small in size, preventing them from being retained on the cathode surface and having a shielding effect, thereby eliminating pinholes and improving the hardness and brightness of the coating.

[0016] The addition of grain refiner, stress reliever and wetting agent can make the coating of the present invention meet the appearance and hardness requirements of hexavalent chromium coating, and avoid the use of toxic hexavalent chromium.

[0017] Advantages of the present invention:

[0018] 1. The average grain size of the Ni-Co-B alloy chromium-substituting coating prepared by the high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution prepared by the present invention is about 10 nm, which is a nanocrystalline coating, and the coating stress is low, and there is no micro cracks after long-term electroplating;

[0019] 2. The hardness of the coating of the present invention after heat treatment can reach 1100-1300 HV-50, and the corrosion resistance is good, the bonding strength between the coating and the substrate is high, and the coating has no cracks;

[0020] 3. The cathode current efficiency of the high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution prepared by the present invention is 95%, and the deposition rate is 70-80 μm / h. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 1 is an X-ray diffraction (XRD) diagram, in which 1 is an X-ray diffraction curve of the plated article prepared in step 3 of Example 1 before heat treatment, 2 is an X-ray diffraction curve of the Ni-Co-B alloy chromium-substituting coating obtained after heat treatment at 200° C. in step 4 of Example 1, and 3 is an X-ray diffraction curve of the Ni-Co-B alloy chromium-substituting coating obtained after heat treatment at 300° C. in step 4 of Example 2;

[0022] Figure 2 This is a SEM image of the Ni-Co-B alloy chromium-substituting coating obtained after heat treatment at 200° C. in step 4 of Example 1;

[0023] Figure 3 This is an optical microscope image of the Ni-Co-B alloy chromium-substituting coating obtained after heat treatment at 200° C. in step 4 of Example 1;

[0024] Figure 4 This is an optical microscope image of the Ni-Co-B alloy chromium-substituting coating obtained after heat treatment at 200° C. in step 4 of Example 1 after being corroded by a 3.5% sodium chloride solution. DETAILED DESCRIPTION

[0025] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0026] Specific implementation method 1: In this implementation method, a high-hardness nano Ni-Co-B alloy chromium replacement electroplating solution is prepared from a main salt, a boron source, an anode activator, a pH buffer, a grain refiner, a stress reliever, a wetting agent and distilled water;

[0027] The main salts are nickel salt and cobalt salt;

[0028] The grain refiner is one of 2-ethylamino-4-methylthiazole-5-carboxylic acid, polyethyleneimine, myrcene, allyl furoate, 3-(methylthio)hexanol acetate or a mixture of several thereof;

[0029] The stress relieving agent is 1,3-dicyclohexyl imidazole chloride, 2-methoxy-4-vinylphenol or Bengal rose red;

[0030] The wetting agent is polyethylene glycol, OP emulsifier or sodium lauryl sulfate.

[0031] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the nickel salt is nickel sulfate and the cobalt salt is cobalt sulfate. The other steps are the same as those of specific implementation method 1.

[0032] Specific embodiment 3: This embodiment differs from specific embodiment 1 or 2 in that: the boron source is dimethylamino borane; the anode activator is nickel chloride; the pH buffer is boric acid. The other steps are the same as those of specific embodiment 1 or 2.

[0033] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the concentration of nickel salt in the high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution is 100-150 g / L, the concentration of cobalt salt is 10-15 g / L, the concentration of boron source is 1-5 g / L, the concentration of anode activator is 20-50 g / L, the concentration of pH buffer is 30-50 g / L, the concentration of grain refiner is 0.1-5 g / L, the concentration of stress reliever is 0.5-1.5 g / L, and the concentration of wetting agent is 0.05-1 g / L. The other steps are the same as those of specific embodiments 1 to 3.

[0034] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that a high-hardness nano Ni-Co-B alloy chromium-substitute electroplating solution is used to prepare a Ni-Co-B alloy chromium-substitute plating layer. The other steps are the same as those of specific embodiments 1 to 4.

[0035] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that a high-hardness nano Ni-Co-B alloy chromium-substitute electroplating solution is used to prepare a Ni-Co-B alloy chromium-substitute coating according to the following steps:

[0036] 1. Preparation of chromium-substitute electroplating solution:

[0037] Dissolving a main salt, a boron source, an anode activator, a pH buffer, a grain refiner, a stress reliever and a wetting agent into distilled water to obtain a chromium replacement electroplating solution;

[0038] 2. pretreating the substrate to obtain a pretreated substrate;

[0039] In step 2, the substrate is immersed in a degreasing liquid at 80 to 90° C., and then rinsed with distilled water; then pickled with hydrochloric acid and rinsed with distilled water to obtain a pretreated substrate;

[0040] 3. Adjust the pH value of the chromium replacement plating solution to 3.5-4.0, immerse the pretreated substrate in the chromium replacement plating solution, and then carry out electroplating at a temperature of 40-50°C and a current density of 2-7A / dm 2 Electroplating under the conditions of , to obtain plated parts;

[0041] 4. High temperature heat treatment:

[0042] The plated part is placed in a tube furnace, and under the protection of argon atmosphere, the plated part is heated to 200-300°C, then kept at 200-300°C, and finally cooled naturally to room temperature to obtain a Ni-Co-B alloy chromium-substituting coating on the surface of the substrate. The other steps are the same as those in the first to fifth embodiments.

[0043] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the degreasing liquid described in step 2 is a mixture of sodium hydroxide, sodium carbonate, sodium phosphate, sodium silicate and distilled water, wherein the concentration of sodium hydroxide is 60-80 g / L, the concentration of sodium carbonate is 20-60 g / L, the concentration of sodium phosphate is 15-30 g / L, and the concentration of sodium silicate is 5-10 g / L; the mass fraction of hydrochloric acid described in step 2 is 10%-20%; the substrate described in step 2 is cold-rolled steel. The other steps are the same as those of specific embodiments 1 to 6.

[0044] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: in step two, the substrate is immersed in a degreasing liquid for 5 to 10 minutes, and after being taken out, it is rinsed with distilled water for 3 to 5 times, then pickled with hydrochloric acid for 3 to 5 times, and rinsed with distilled water for 3 to 5 times to obtain a pretreated substrate. The other steps are the same as those of specific embodiments one to seven.

[0045] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that the electroplating time in step 3 is 30 to 180 minutes. The other steps are the same as those in specific embodiments 1 to 8.

[0046] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the insulation time in step 4 is 1 h to 2 h, and the heating rate in step 4 is 5°C / min to 10°C / min. The other steps are the same as those in specific embodiments 1 to 9.

[0047] The following examples are used to verify the beneficial effects of the present invention:

[0048] Example 1: A high-hardness nano Ni-Co-B alloy chromium substitute electroplating solution is used to prepare a Ni-Co-B alloy chromium substitute coating according to the following steps:

[0049] 1. Preparation of chromium-substitute electroplating solution:

[0050] Dissolve NiSO4·6H2O, CoSO4·7H2O, NiCl2·6H2O, boric acid, dimethylaminoborane, 2-ethylamino-4-methylthiazole-5-carboxylic acid, 2-methoxy-4-vinylphenol and sodium dodecyl sulfate in distilled water to obtain a chromium-substituting electroplating solution;

[0051] The chromium-substituting electroplating solution in step 1 has a NiSO4·6H2O concentration of 120 g / L, a CoSO4·7H2O concentration of 12 g / L, a NiCl2·6H2O concentration of 40 g / L, a boric acid concentration of 35 g / L, a dimethylaminoborane concentration of 3 g / L, a 2-ethylamino-4-methylthiazole-5-carboxylic acid concentration of 3 g / L, a 2-methoxy-4-vinylphenol concentration of 1 g / L, and a sodium dodecyl sulfate concentration of 0.1 g / L;

[0052] 2. pretreating the substrate to obtain a pretreated substrate;

[0053] In step 2, the substrate is immersed in a degreasing liquid at 90° C. for 5 minutes, taken out and rinsed with distilled water for 5 times, then pickled with 15% hydrochloric acid for 3 times, and rinsed with distilled water for 5 times to obtain a pretreated substrate;

[0054] The degreasing liquid described in step 2 is a mixture of sodium hydroxide, sodium carbonate, sodium phosphate, sodium silicate and distilled water, wherein the concentration of sodium hydroxide is 60 g / L, the concentration of sodium carbonate is 30 g / L, the concentration of sodium phosphate is 20 g / L, and the concentration of sodium silicate is 8 g / L;

[0055] The substrate described in step 2 is cold-rolled steel;

[0056] 3. Adjust the pH value of the chromium replacement plating solution to 3.5-4.0, immerse the pretreated substrate in the chromium replacement plating solution, and then 2 Electroplating for 30 minutes under the conditions of , to obtain plated parts;

[0057] 4. High temperature heat treatment:

[0058] The plated part is placed in a tube furnace, and under the protection of an argon atmosphere, the temperature of the plated part is increased to 200°C at a heating rate of 10°C / min, and then kept at 200°C for 1 hour, and finally naturally cooled to room temperature to obtain a Ni-Co-B alloy chromium-substituting coating on the surface of the substrate.

[0059] The XRD patterns of the plated parts obtained in this embodiment before and after heat treatment are compared. Figure 1 As shown, it indicates that the grains grow preferentially along the (111) crystal plane. By comparison, it can be found that after heat treatment, the half-peak width of the diffraction peak corresponding to Ni (111) of the coating becomes smaller, and the peak intensity gradually increases. The results show that during heat treatment, due to the coarsening of grains and the precipitation of tiny intermetallic compounds, the hardness increases rapidly.

[0060] Figure 1 1 is an X-ray diffraction (XRD) diagram, in which 1 is an X-ray diffraction curve of the plated article prepared in step 3 of Example 1 before heat treatment, 2 is an X-ray diffraction curve of the Ni-Co-B alloy chromium-substituting coating obtained after heat treatment at 200° C. in step 4 of Example 1, and 3 is an X-ray diffraction curve of the Ni-Co-B alloy chromium-substituting coating obtained after heat treatment at 300° C. in step 4 of Example 2;

[0061] Furthermore, when the grain size is between 1 and 100 nm, the average grain size can be calculated using the Scherrer formula, as shown below:

[0062]

[0063] Where d is the average grain size (nm);

[0064] λ——X-ray wavelength (λ=0.154nm);

[0065] K——Scherrer constant (K=0.89);

[0066] B——Full width at half maximum of diffraction peak;

[0067] θ—Bragg diffraction angle;

[0068] After calculation, the average grain size is 10.26nm, proving that the coating is a nano coating. The hardness value is 1210HV-50.

[0069] Figure 2 This is a SEM image of the Ni-Co-B alloy chromium-substituting coating obtained after heat treatment at 200° C. in step 4 of Example 1;

[0070] Figure 3This is an optical microscope image of the Ni-Co-B alloy chromium-substituting coating obtained after heat treatment at 200° C. in step 4 of Example 1;

[0071] Figure 2 and Figure 3 The surface is dense and flat, and the hard phase is evenly distributed.

[0072] Example 2: The difference between this example and Example 1 is that in step 4, the plated part is placed in a tube furnace, and under the protection of an argon atmosphere, the plated part is heated to 300°C at a heating rate of 10°C / min, and then kept at 300°C for 1 hour, and finally naturally cooled to room temperature to obtain a Ni-Co-B alloy chromium-substituting coating on the surface of the substrate. The other steps and parameters are the same as those in Example 1.

[0073] The XRD of the coating obtained in Example 2 is shown in Figure 1 As shown;

[0074] from Figure 2 It can be found that at this time, the coating also appears in a crystalline state, which improves the hardness of the coating.

[0075] Furthermore, the average size of the grains was calculated by the Scherrer formula. In Example 2, the average size of the grains was 9.38 nm, proving that the coating was a nano-coating. The hardness value was 1290 HV-50.

[0076] Comparative Example: The difference between this example and Example 1 is that: In step 1: preparing a chromium-substitute electroplating solution:

[0077] Dissolve NiSO4·6H2O, CoSO4·7H2O, NiCl2·6H2O, boric acid and dimethylamino borane in distilled water to obtain a chromium-substituting electroplating solution; the concentration of NiSO4·6H2O in the chromium-substituting electroplating solution described in step 1 is 120 g / L, the concentration of CoSO4·7H2O is 12 g / L, the concentration of NiCl2·6H2O is 40 g / L, the concentration of boric acid is 35 g / L, and the concentration of dimethylamino borane is 3 g / L. Other steps and parameters are the same as those in Example 1.

[0078] The grain size of the coating prepared in the comparative example is 100.4 nm, and the hardness value is 698 HV-50. This further illustrates that the grain refiner, stress reliever and wetting agent of the present invention play a significant role in reducing the crystal size and improving the hardness of the coating.

Claims

1. A high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution, characterized in that A high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution is prepared from a main salt, a boron source, an anode activator, a pH buffer, a grain refiner, a stress reliever, a wetting agent and distilled water; The main salts are nickel salt and cobalt salt; The grain refiner is 2-ethylamino-4-methylthiazole-5-carboxylic acid; The stress reliever is 2-methoxy-4-vinylphenol; The wetting agent is sodium lauryl sulfate; The nickel salt is nickel sulfate; the cobalt salt is cobalt sulfate; The boron source is dimethylamino borane; the anode activator is nickel chloride; the pH buffer is boric acid; The high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution has a nickel salt concentration of 100-150 g / L, a cobalt salt concentration of 10-15 g / L, a boron source concentration of 1-5 g / L, an anode activator concentration of 20-50 g / L, a pH buffer concentration of 30-50 g / L, a grain refiner concentration of 0.1-5 g / L, a stress reliever concentration of 0.5-1.5 g / L, and a wetting agent concentration of 0.05-1 g / L.

2. The use of a high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution as claimed in claim 1, characterized in that A high-hardness nano Ni-Co-B alloy chromium substitute electroplating solution is used to prepare a Ni-Co-B alloy chromium substitute coating. The Ni-Co-B alloy chromium substitute coating has an average grain size of 10 nm and is a nanocrystalline coating.

3. The use of a high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution according to claim 2, characterized in that A high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution is used to prepare a Ni-Co-B alloy chromium-substituting coating according to the following steps:

1. Preparation of chromium-substitute electroplating solution: Dissolving a main salt, a boron source, an anode activator, a pH buffer, a grain refiner, a stress reliever and a wetting agent into distilled water to obtain a chromium replacement electroplating solution; 2. pretreating the substrate to obtain a pretreated substrate; In step 2, the substrate is immersed in a degreasing liquid at 80-90°C, and then taken out and rinsed with distilled water; Then, the substrate is pickled with hydrochloric acid and rinsed with distilled water to obtain a pretreated substrate; 3. Adjust the pH value of the chromium replacement plating solution to 3.5~4.0, immerse the pretreated substrate in the chromium replacement plating solution, and then heat at a temperature of 40℃~50℃ and a current density of 2~7A / dm 2 Electroplating under the conditions of , to obtain plated parts; 4. High temperature heat treatment: The plated part is placed in a tube furnace, and under the protection of an argon atmosphere, the temperature of the plated part is raised to 200-300°C, and then kept at 200-300°C, and finally naturally cooled to room temperature to obtain a Ni-Co-B alloy chromium-substituting coating on the surface of the substrate.

4. The use of a high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution according to claim 3, characterized in that The degreasing liquid described in step 2 is a mixture of sodium hydroxide, sodium carbonate, sodium phosphate, sodium silicate and distilled water, wherein the concentration of sodium hydroxide is 60-80 g / L, the concentration of sodium carbonate is 20-60 g / L, the concentration of sodium phosphate is 15-30 g / L, and the concentration of sodium silicate is 5-10 g / L; the mass fraction of the hydrochloric acid described in step 2 is 10%-20%; the substrate described in step 2 is cold-rolled steel.

5. The use of a high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution according to claim 3, characterized in that In step 2, the substrate is immersed in the degreasing liquid for 5 minutes to 10 minutes, and after being taken out, it is rinsed with distilled water for 3 to 5 times, then pickled with hydrochloric acid for 3 to 5 times, and rinsed with distilled water for 3 to 5 times to obtain a pretreated substrate.

6. The use of a high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution according to claim 3, characterized in that The electroplating time described in step 3 is 30 to 180 minutes.

7. The use of a high-hardness nano Ni-Co-B alloy chromium-substituting electroplating solution according to claim 3, characterized in that The insulation time described in step 4 is 1h~2h; the heating rate described in step 4 is 5℃ / min~10℃ / min.

Citation Information

Patent Citations

  • Electric deposition preparation method of Ni-Co-B alloy substituted hard chromium plating

    CN102352522A